Exploring the genetic factors affecting the craniofacial morphology of Egyptian ancestry - Mohamed ADEL; Lorri Ann MORFORD; James Kennedy HARTSFIELD; Jr; Yu HIKITA; Reina HATANAKA; Koutaro MAKI; Tetsutaro YAMAGUCHI (Kanagawa Shigaku, 2021)
[Abstract] The origin of the Egyptian race is a controversial subject and a variety of views have emerged from the theories proposed by Egyptologists based on their studies about ancient Egyptian history. In this review, we will discuss the unique craniofacial characteristics of modern Egyptians based on cephalometric images and compare these characteristics with those of populations that are believed to be the origin of the Egyptian race. Furthermore, we will discuss the effect of genetic variations in the growth hormone receptor (GHR) and fibroblast growth factor receptor 1 (FGFR1) genes on the craniofacial morphology of the Egyptian population and compare it with that of populations with other ancestries.